Atypical site of nasopharyngeal branchial cleft cyst: A case of an unusual age presentation - Salma S Alsharhan; Aishah A Alghuneem; Danah F Alrusayyis; Marwah S Aljahli (Wolters Kluwer Medknow Publications, 2023)
Nasopharyngeal branchial cleft cysts (NBC) are generally single, unilateral, and asymptomatic. They may get infected or produce obstructive symptoms as it enlarges. The definitive diagnosis is usually confirmed by Magnetic resonance imaging (MRI) and histopathology. A 54-year-old male patient presented with progressive bilateral nasal obstruction, more on the right side, associated with hyponasal voice and postnasal discharge of 2 years' duration. A cystic mass was found by nasal endoscopy on the lateral right side of the nasopharynx, extending to the oropharynx, and was confirmed with MRI findings. Uneventful total surgical excision and marsupialization were done with follow up of nasopharyngeal endoscopic examination on each visit. The pathological features and the site of the cyst were compatible with a second branchial cleft cyst. Although rare, NBC should be considered one of the differential diagnoses of nasopharyngeal tumors. Surgical excision and marsupialization are the main treatment with low complication and recurrence rates.